A QoS framework for connection services in Parlay - Bata, Yusuf (My University, 2008)
Abstract Most applications using network connection services require information to be transferred within specific constraints (or Quality of Service). Parlay enables applications to access functionality of underlying networks while preserving network integrity. Connection service functionality of underlying networks is currently provided to applications by Parlay in the Call Control and Data Session Control SCFs. Parlay does not however provide access to the QoS functionality of connection services although this functionality may be provided by networks. This report presents the design, specification and simulation of a QoS framework for connection services provided by Parlay. The QoS framework provides applications with access to the QoS functionality of connection services in the underlying networks. The design is divided into 3 parts (or models): the object model (defines the objects that make up the QoS framework), the information model (deals with how objects specify QoS and mappings between different QoS specifications), and the interaction model (defines how objects interact). A formal, technology-independent specification of the QoS framework is presented using UML. The specification is composed using the three parts of the design. A simulation of the QoS framework presented in this report is also described to validate the framework. The simulation is a multi-threaded, distributed CORBA application implemented in JAVA (Java SDK version 1.5) and is based on the UML specification of the QoS framework. Details about the simulation design and implementation are summarised in this report. The QoS framework provides per-application, per-connection QoS support for Parlay’s connection services, supports existing and future Parlay connection services, follows existing Parlay design paradigms, and co-exists with and makes use of existing and future Parlay infrastructure. Parlay guidelines relating to permitted changes are followed strictly in the design of the QoS framework, which ensures the backward compatibility of Parlay if the QoS framework is added to the Parlay API. All Parlay design guidelines are also followed to allow for the easy integration of the QoS framework into the Parlay API. The simulation validates that the design of the QoS framework is: complete (in terms of specification), realistic, compatible with a standard Parlay implementation (JAVA and CORBA), and scalable (easy integration of new connection services).
Keywords: QoS; Frameworks; Parlay; OSA